Synthesis, crystal structures and competitive binding property of a family of calix[4]arene-biscrown-5/6 and their application in extraction of alkali metal ions from sea bittern. (24th November 2015) - Ramakrishna, Vallu; Suresh, E.; Boricha, Vinod P.; Bhatt, Anjani K.; Paul, Parimal
Graphical abstract: Competitive metal ion binding property of a family of calix-crown hybrid ionophore has been reported. 1 H NMR, ITC and crystal structure studies were carried out for structure elucidation and to determine thermodynamic parameters for complexation. The ionophores were applied for extraction of K + from a natural source such as sea bittern. Abstract: A family of calix[4]arene compounds containing crown moieties at both the upper and lower rims of the calix unit with different substituents attached to the nitrogen atom of the aza-crown moiety have been synthesized, characterized and their competitive binding property towards Li +, Na +, K +, Mg 2+, Ca 2+ and Sr 2+ in aqueous media has been investigated. These ionophores exhibit high selectivity towards K +, assessed by two-phase extraction method followed by ion chromatographic assay of the metal ions in the extract. Isothermal calorimetric titration for complex formation with K + was carried out to evaluate stoichiometry, binding constant and other thermodynamic parameters (Δ H, Δ S and Δ G ). For structural elucidation in solution, detail 1 H NMR study was carried out and K + complexes were isolated for solid state characterization. Molecular structures of two of the ionophores and K + -complex of one of the ionophores has been established by single crystal X-ray study. 1 H NMR, ITC and single crystal XRD studies suggest 1:1 complex formation with encapsulation of K + in the crown-6 ring at the upper rim. These ionophores have been applied for extraction of metal ions from bittern.